Efeito de borda sobre uma assembléia de pequenos mamíferos em um fragmento de floresta estacional decidual de Santa Maria, RS, Sul do Brasil - Finokiet, Manuela (2007)
Alterations caused by the edge effects in a fragment have direct influence over the fauna and can determine the composition and distribution of the small non-flying mammals assemblage in a landscape. This study had as aim of analyzing the edge effect over the structure of a small mammal assemblege and the circumjacent environment in a decidual forest fragment located in the southern limit of the Atlantic Forest, in the center state of Rio Grande do Sul. Five field phases were carried out, with an effort of 6360 trap-night, and 1060 pitfall-night, totalizing 78 captured individuals (99 captures), belonging to four species of rodents and two species of marsupials. The success of capture of live traps was 1.2% and of pitfall traps was of 2.3%. Rodents were responsible for 97.4% of all captures and marsupials, 2.6%. In pitfall traps, it was observed high abundance of rodents in the interior in relation to the edge. The Analysis of Multivariada Variance by Randomization showed that there is no significant difference in the composition of species in relation to distances of the edge, despite the Analysis of Principal Components has evidenced some trends, grouping the species in accordance to the distances where they had occurred more frequently. Thus, the assemblege of small mammals was dominated by a species of rodent, Oligoryzomys nigripes, which represented 73% of all captures, appearing in all distances of the edge, but mostly in the forest interior. On the other hand, marsupials appeared only in the interior of the fragment, being A. montensis registered from 130 m from the edge, seeming to prefer habitats with denser forest cover. By using MANOVA, and on the basis of the biotic and abiotic factors analyzed along the edge gradient, it was possible to establish different distances of penetration of the edge that had varied from 10 to 160 meters. The Congruence Analysis showed that environmental variables which best explained the distribution of small mammas in the gradient was the feeding resources, lianas, trees and canopy cover. Thus, species of small mammals seem to use the modified environment in accordance to their adaptations to the available micro-habitats in the gradient edge-interior, having a noticeable edge effect in the study area.